STRATEGI PEMASARAN POLITIK CALEG PEMULA ERI IRAWAN DALAM MEMBANGUN CITRA POLITIK DI KOTA SURABAYA - Suriyadi Putra, Andre Muslim; Rizqi, Muchamad; Prayogo, Moh Dey (Sintesa, 2025)
ABSTRACT This study focuses on digging deeper into how the political communication strategies of politicians build their image in the eyes of the public, by using the concept of political marketing it will certainly make it easier for political actors to build an image in the eyes of the public, there are several indicators that support political actors in building an image including: publicity, political campaigns, and personal branding. By using a descriptive qualitative research method, researchers will get answers by interviewing one of the political actors in Surabaya, in the results of the study there are several aspects and stages that drive an image of political actors such as going directly to the field and building cooperation with local community leaders, in addition to building cooperation with local community leaders, political actor Eri Irawan also builds a conclusion of the relationship long before the election period begins so that it is easier to be recognized by the public. In conclusion, Eri Irawan's political image has been formed long before entering the world of politics because Eri Irawan has gone into the field by helping the community in solving social problems in his area. Keywords: Political Communication, Political Marketing, Political Campaings, Eri Irawan, Image of Political